Penegakan Hukum terhadap Tindak Pidana Korupsi dalam Pertambangan Panas Bumi di Indonesia - Maman Nurohman (Savana, 2024)
In 2023, Indonesia had a corruption perception index score of 34 and was ranked 115th out of 180 countries (Transparency International). The purpose of the research conducted by the author is to determine how the regulation and implementation of corruption in the geothermal mining sector in Indonesia is based on decision number 60/Pid.Sus-TPK/2023/PN.Jkt.Pst. This study uses the juridical normative research method. The results of the study indicate that the Panel of Judges examining case number 60/Pid.Sus-TPK/2023/PN.Jkt.Pst. has determined that the decision is not in accordance with applicable provisions. The conclusions are: 1) Geothermal mining is regulated by Law Number 21 of 2014 concerning Geothermal, while corruption is regulated by Law Number 20 of 2001, which is an amendment to Law Number 31 of 1999 concerning the Eradication of Corruption. 2) The implementation of the provisions on corruption crimes in Decision Number 60/Pid.Sus-TPK/2023/PN.Jkt.Pst. does not comply with existing regulations.